Dinamika Hukum Perlindungan Anak Luar Nikah di Indonesia - Jakobus Anakletus Rahajaan; Sarifa Niapele (Univiversitas Dr. Djar Wattiheluw, 2021)
This study aims to analyze the dynamics of legal protection for children out of wedlock with normative juridical research methods. The results of the study are that, during the 76 years of Indonesia's independence, the State's concern for children out of wedlock is very less. It is proven by various laws and regulations that absolutely do not provide certainty, justice and legal benefits for children out of wedlock, and this reality is not in accordance with the principles of the declaration of human rights, the principle of a state of law based on Pancasila and the principle of equality before the law. However, a very advanced and phenomenal legal breakthrough emerged, namely the Constitutional Court's decision no. 46/PUU- VIII/2010 which gives the status, position and rights of legitimate children to children out of wedlock. This should be appreciated as a spectacular step to make the law a sosial engineering tool to break down misconceptions about children out of wedlock. By supporting the Constitutional Court's decision, we have upheld the values of human rights, Pancasila and the principle of Equality before the Law of the State of Law which must provide certainty, justice and legal benefits for every citizen without indiscriminate or discrimination. The Constitutional Court's decision can cause a domino effect for children out of wedlock, adulterers, and society. It is time for the dynamics of the law to develop so, where the law is expected to become a sosial engineering tool that will change the paradigm and treatment of society towards children out of wedlock.